2011
DOI: 10.1097/mpg.0b013e3182212130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long‐term Parenteral Nutrition on Serum Lipids, Plant Sterols, Cholesterol Metabolism, and Liver Histology in Pediatric Intestinal Failure

Abstract: Serum PS moderately increase during olive oil-based PN, and correlate positively with PN% and glutamyl transferase. Despite well-preserved liver function, histology often revealed significant liver damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 44 publications
5
69
0
1
Order By: Relevance
“…These fi ndings suggest that IL-induced intrahepatic accumulation of conjugated bile acid is associated with biliary injury, which may precede hepatocellular injury. Direct examination of the liver showed hepatomegaly in all TPN groups compared with enteral formula feeding, consistent with our previous reports ( 4,26 ). Livers from all TPN pigs showed evidence of histopathological injury, including biliary duct dilation, portal tract cellular infi ltration, and microvascular steatosis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These fi ndings suggest that IL-induced intrahepatic accumulation of conjugated bile acid is associated with biliary injury, which may precede hepatocellular injury. Direct examination of the liver showed hepatomegaly in all TPN groups compared with enteral formula feeding, consistent with our previous reports ( 4,26 ). Livers from all TPN pigs showed evidence of histopathological injury, including biliary duct dilation, portal tract cellular infi ltration, and microvascular steatosis.…”
Section: Discussionsupporting
confidence: 90%
“…However, the histological scores suggested that the features biliary injury and infl ammation were highest among the IL versus other lipid emulsion groups. Mouse models of cholestasis have shown blunted histological hepatotoxicity with fi sh oil ( 26,27 ). Collectively, these results suggest that fi sh oil-containing emulsions prevent the development of PNALD in TPN-fed neonatal pigs.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Thus, we hypothesized that saturated fatty acids augment TRB3 expression under conditions of ER stress and lead to apoptosis in human liver cells. It has previously been shown that the effect of TRB3 on survival or apoptosis are dependent on the cell type and context [18,23,30,31,32,33,34]. Here, we have demonstrated for the first time that TRB3 is significantly increased at the protein and mRNA level during palmitate-induced ER stress in the normal human liver cell line, L02, and that this higher expression level is associated with increased apoptosis.…”
Section: Discussionsupporting
confidence: 49%
“…La solución de lípidos procedente de soja (Intralipid ® ) fue sustituida en las unidades pediátricas europeas por otras soluciones basándose en el desequilibrio en AGE por exceso de omega-6 y en la hepatotoxicidad (29) debida a la peroxidación lipídica y al efecto de los fitosteroles (30,31). Las soluciones mixtas de LCT y MCT (Lipofundina MCT/LCT 20% ® ) han sido administradas durante tiempo siendo bien toleradas incluso en lactantes pequeños (1).…”
Section: Requerimientos De Lípidosunclassified